Applying university-industry collaboration and organizational context to speed up innovation in biotechnological industry in Malaysia - Hamdi, Shabnam; Silong, Abu Daud (2011)
This study will examine university- industry collaboration and organizational context to speed up innovation with mediating role of technology uncertainly in Malaysian biotechnological industry. It considers two aspects of uncertainty technology novelty and technology turbulence. The development of a country’s economy is strongly linked to its technological activities. The government of Malaysia has recognized the need to facilitate university and industry linkage to speed up the technology development from idea to commercialization. This paper describe and discuss the importance of organizational contextual factors surrounded a research team and virtual effect of university industry collaboration to speed up new product development.